(untitled) (Biological Sciences - PJSIR, 1995)
Soybean is an important leguminous oil crop and a major source of protein. Natural nodulation is poor in the Peshawar valley but artificial inoculation with Bradyrhizobium japo- nicum increases growth and bean yield [1]. The present studies were conducted to see the effect of inoculation with four rhizobial strains on growth, yield and N2-fixing parame- ters in Bragg variety of soybean, which is adapted to this location.